2020
DOI: 10.1109/access.2020.2988072
|View full text |Cite
|
Sign up to set email alerts
|

Co-Located Self-Neutralized Handset Antenna Pairs With Complementary Radiation Patterns for 5G MIMO Applications

Abstract: In this paper, 4 × 4 / 8 × 8 / 10 × 10 multiple input multiple output (MIMO) antenna systems composed of co-located self-neutralized antenna pairs are proposed to operate at 4.8-5.0 GHz (part of N77 band) for the fifth-generation (5G) communication applications. The proposed antenna pairs consist of a loop antenna and a monopole antenna, co-locating together with a compact size of 6.7 × 15.5 × 3.08 mm 3 . Meanwhile, the co-located design can miniaturize 50% of the antenna size, which is quite significant for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Many decoupling techniques with specific structures have been proposed in 5G communication such as the decoupling network, 3 neutralization line, 4‐7 multimode decoupling, 8 and electromagnetic bandgap structure 9,10 . Above methods can effectively improve antenna isolation, yet some of the complex decoupling structures occupies much space and will course amounts of deterioration in radiation which leads to low antenna efficiency (>30% in Reference 7, >38% in Reference 8, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many decoupling techniques with specific structures have been proposed in 5G communication such as the decoupling network, 3 neutralization line, 4‐7 multimode decoupling, 8 and electromagnetic bandgap structure 9,10 . Above methods can effectively improve antenna isolation, yet some of the complex decoupling structures occupies much space and will course amounts of deterioration in radiation which leads to low antenna efficiency (>30% in Reference 7, >38% in Reference 8, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…With the allocation of the 3.5 GHz (3.4-3.6 GHz) band for 5G wireless communication [5], the sub-6 GHz MIMO antenna systems have been popularly studied to allow more antenna elements to be integrated into space-scarce terminal devices [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It has been demonstrated that high isolation (i.e., low mutual coupling) and low correlation are essential figure-of-merits for MIMO antenna systems to guarantee excellent radiation performance and diversity property.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the previously reported techniques for the sub-6 GHz 5G MIMO antennas can be categorized into the following two categories: decoupled MIMO antenna arrays by utilizing decoupling structures [6][7][8][9][10][11][12] and selfdecoupled MIMO antenna arrays without any additional structures [13][14][15][16][17][18][19][20][21][22][23]. For the decoupled MIMO antenna arrays, the frequently adopted decoupling structures include neutralization lines or decoupling networks [6][7][8][9], and additional resonators [9][10][11][12], which require additional occupation and complicated tuning efforts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is of such great interest yet a significant challenge to design MIMO antenna systems with high integration, miniaturized volume, low interference, and low correlation; this is especially true in terminal devices due to size limitation and placement constraint. In the literature, the most recent studies focused on the realization of selfdecoupled compact MIMO antenna sets using polarization or pattern control and on their duplication for the sake of N × N MIMO arrays [4][5][6][7][8][9][10][11][12][13][14][15]; otherwise, other research investigated decoupled MIMO antenna arrays by introducing decoupling structures [16][17][18][19][20][21][22], while the rest relies on the spatial distance to realize optimized arrangement of the MIMO antenna arrays [23][24][25][26][27][28][29][30]. These methods usually suffer from complicated installment, massive structures, or relatively large separations between antenna elements.…”
mentioning
confidence: 99%